Is 10/12 Fr Ureteral Access Sheath more Suitable for Flexible Ureteroscopic Lithotripsy? - Li, Wenfeng; Mao, Yuanshen; Gu, Yufei; Lu, Chao; Gu, Xin; Hua, Bao; Pan, Weixin; Xi, Qinghong; Wang, Zhong (Urology Journal, 2021)
Purpose: To choose the ideal ureteral access sheath (UAS) size for an unstented ureter in flexible ureteroscopic lithotripsy (FURL). Materials and Methods: A retrospective study was conducted in patients treated with FURL for renal calculi from 2005 to 2020. The patients were divided into two groups: smaller (10/12 Fr) vs. larger (12/14 Fr) calibre UAS. The outcomes were the insertion success rate, systemic inflammatory response syndrome (SIRS) complication rate after the operation, ureteral wall injury, operative time, and stone-free rate. Results: Of the 1573 patients enrolled, 10/12 Fr UAS was used in 957 patients (Group A), and 12/14 Fr UAS was used in the remaining patients (Group B). The insertion success rate was significantly better in Group A (91.2% vs. 86.9%, P = .006), with no significant difference between the groups regarding the stone-free rate, postoperative pain, operative time or hospital stay. The severity of visible ureteral lesions with 10/12 Fr UAS was significantly lower than that with larger UASs (80.1% vs 85.2%, P < .001). Despite the lack of a significant difference in the incidence of SIRS between the two groups, the incidence of SIRS in the 10/12 Fr group showed a sharp increase with stones > 2 cm (17.0% vs. 8.5%, P = 0.037). Conclusion: The use of 10/12 Fr UAS was beneficial with respect to insertion success rate, avoiding ureteral wall injury and not increasing postoperative infectious complications in FURL. We recommend the use of a smaller calibre (10/12 Fr) UAS in patients with renal calculi < 2 cm.